2009
DOI: 10.1088/0004-637x/698/2/2075
|View full text |Cite
|
Sign up to set email alerts
|

IRAS-BASED WHOLE-SKY UPPER LIMIT ON DYSON SPHERES

Abstract: A Dyson Sphere is a hypothetical construct of a star purposely cloaked by a thick swarm of broken-up planetary material to better utilize all of the stellar energy. A clean Dyson Sphere identification would give a significant signature for intelligence at work. A search for Dyson Spheres has been carried out using the 250,000 source database of the IRAS infrared satellite which covered 96% of the sky. The search has used the Calgary database for the IRAS Low Resolution Spectrometer (LRS) to look for fits to bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 26 publications
0
55
0
Order By: Relevance
“…Unfortunately, despite some searches, the results are negative (Jugaku, Noguchi, and Nishimura 1995;Carrigan Jr 2009;Wright et al 2014). We thus lack proof or even indication of ETI, a fundamental gap in our knowledge of the universe.…”
Section: -Introductionmentioning
confidence: 93%
“…Unfortunately, despite some searches, the results are negative (Jugaku, Noguchi, and Nishimura 1995;Carrigan Jr 2009;Wright et al 2014). We thus lack proof or even indication of ETI, a fundamental gap in our knowledge of the universe.…”
Section: -Introductionmentioning
confidence: 93%
“…Waste Heat A mid-infrared map with sufficiently high sensitivity might allow one to conduct a waste heat search for civilizations (Dyson 1960;Carrigan 2009;Wright et al 2014a) by looking for industrial heat signatures on the planetary surface. For instance, Kuhn and Berdyugina (2015) suggested that a 70m telescope might be sufficient to detect the rotationally modulated localized output of industry on an Earth-like planet for a civilization with ∼ 25 times the energy supply of humanity (which is equal to about 1% of light the planet intercepts from its star).…”
Section: Technosignatures On Exoplanets and The Host Starsmentioning
confidence: 99%
“…Many of the past searches for Dyson Spheres have focused on detecting the presence of structures around individual stars within the Milky Way (for example, Refs. [5,21,22]).…”
Section: New Observational Signatures Of Advanced Civilizationsmentioning
confidence: 99%